TEMPERATURE MONITORING AND PERIOPERATIVE HEAT LOSS - Khan, Shehzad Akbar; Aurangzeb, Mahmood; Zarin, Muhammad; Khurshid, Muhammad (Journal of Postgraduate Medical Institute, 2011)
Objectives: To assess the temperature fall at various stages in the perioperative period and identification of contributing factors. Material & Methods: This observational study was carried out at Blackpool Victoria Hospital, UK from August 2005 – January 2006 on 32 patients undergoing major lower limb vascular surgery. Semistructured data collection form was designed to record the time and tympanic temperature at different stages in perioperative period and the warming methods used. Results: A median fall of 0.1oC (0 - 0.5oC) in core temperature was recorded in ward and theatre reception area. The median fall of temperature in the anaesthetic room was 0.3oC (0-.8oC). Patients (n=16) spending more than ½ hour in the anaesthetic room had a significant (p=0.002) temperature drop recorded at 0.4oC as compared to 0.2oC for those spending less than 30 minutes. During operation, a median fall of temperature by 0.8oC (0.3 – 2.1oC) was recorded. Operations lasting for 21/ hours or more (n=16) resulted 2 in a 1oC temperature fall as against 0.5oC for the rest. Seven patients, in whom a warming mat was used, had a temperature drop of 0.6oC compared to 0.35oC in patients who received warm touch. In the recovery unit, 23 patients had a further drop of 0.3oC, while 9 patients who were actively warmed gained 0.6oC. Conclusions: Significant heat loss occurs in the anaesthetic room relevant to the length of time consumed in anaesthetising the patient. Furthermore active warming measures in the perioperative period have a positive impact on maintaining core temperature.